2010
DOI: 10.1111/j.1460-9592.2010.03262.x
|View full text |Cite
|
Sign up to set email alerts
|

A new approach for peri‐operative analgesia of cleft palate repair in infants: the bilateral suprazygomatic maxillary nerve block

Abstract: BMB using a suprazygomatic approach seems to improve pain relief, to decrease peri-operative consumption of opioids, and to favor early feeding resumption after CP repair in infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
103
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(107 citation statements)
references
References 11 publications
(28 reference statements)
3
103
0
1
Order By: Relevance
“…The literature is replete with the use of adjunct medications and regional injection techniques in an attempt to decrease overall narcotic use. [2][3][4][5][6] Comparisons also extend to the type of narcotic used. 7 Our experience with iliac crest harvesting analgesia led us to believe that by soaking a hemostatic pledget with bupivacaine, we could improve long-term analgesia, earlier return of oral intake, and earlier discharge from the hospital.…”
Section: Discussionmentioning
confidence: 98%
“…The literature is replete with the use of adjunct medications and regional injection techniques in an attempt to decrease overall narcotic use. [2][3][4][5][6] Comparisons also extend to the type of narcotic used. 7 Our experience with iliac crest harvesting analgesia led us to believe that by soaking a hemostatic pledget with bupivacaine, we could improve long-term analgesia, earlier return of oral intake, and earlier discharge from the hospital.…”
Section: Discussionmentioning
confidence: 98%
“…13,40 Akin to the studies advocating the integration of peripheral nerve blocks in perioperative pain for patients undergoing cleft lip repair, 41,42 recent studies have also reported successful use of a suprazygomatic maxillary nerve block for patients undergoing cleft palate repair to facilitate more prompt return to oral feeding and decreased use of narcotics. 43 Further investigations potentially incorporating those pain management adjuncts may help determine with better validity their value in reducing hospital length of stay.…”
Section: Discussionmentioning
confidence: 99%
“…A double-blinded, randomized study also demonstrated a signifi cant reduction in analgesia requirement and pain score in children who had an infraorbital nerve block compared to the conventional peri-incisional infi ltration by the surgeon [ 18 ]. Recently, Mesnil et al [ 19 ] observed the effectiveness of bilateral maxillary nerve blocks using a suprazygomatic approach, fi nding improved pain relief and a reduction in opioid consumption following cleft palate repair in infants. Furthermore, this approach minimizes the likelihood of entering the orbit and reduces the risk of vascular injury as the needle enters the infratemporal fossa and ultimately the sphenopalatine fossa in a superior-to-inferior direction.…”
Section: Current Literature In Ultrasoundguided Approachesmentioning
confidence: 94%
“…Using electrical stimulation, Mesnil et al [ 19 ] showed that the disappearance of the temporal muscle twitch coincided with the needle's tip in the pterygopalatine fossa where local anesthetic was injected. More recently, this group successfully published a randomized, double-blind study evaluating an ultrasound-guided suprazygomatic maxillary nerve block [ 21 ].…”
Section: Current Literature In Ultrasoundguided Approachesmentioning
confidence: 99%
See 1 more Smart Citation